PENERAPAN POISSON INVERSE GAUSSIAN REGRESSION UNTUK MEMODELKAN LAMA RAWAT INAP PASIEN DEMAM BERDARAH DENGUE (DBD) UPTDK. RSU. HAJI MEDAN PEMERINTAHAN PROVINSI SUMATERA UTARA - Khairul Purqon; Rina Widyasari; Ismail Husein (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Dengue fever is one of the dangerous diseases that can threaten human life if not treated seriously. Dengue hemorrhagic fever is one of the health problems that exist in the community where the number of sufferers tends to increase and the spread is very wide. Dengue hemorrhagic fever (DHF) is a disease caused by infection with the DEN-1, DEN-2, DEN-3 or DEN-4 viruses transmitted to the bite of Aedes aegypti and Aedes Albopictus mosquitoes before it was infected by the dengue virus by dengue sufferers. Aedes aegypti mosquitoes become more infective for 8-12 days after sucking blood from dengue patients before. However, for now only researchers take only a few factors that make the length of stay of dengue patients in UPTDK. RSU. Hajj Medan Government of North Sumtera Province. In this study, the independent variables used were Patient Age Value (),  Platelet value (), Leukocyte value (),  and Hemoglobin value () in UPTDK. RSU. Haji Medan Government of North Sumtera Province using Poisson Inverse Gaussian Regression (PIGR). Poisson Inverse Gaussian Regression (PIGR) is a form of regression from mixed poisson designed on enumeration data with overdispersion cases. Therefore, research using the Poisson Inverse Gaussian Regression method can be carried out. The Poisson Inverse Gaussian Regression model formed is  with a very significant influential variable is the Leukocyte value